2020
DOI: 10.3390/ijms21186939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute and Prolonged Inflammation on the Gene Expression of Proinflammatory Cytokines and Their Receptors in the Anterior Pituitary Gland of Ewes

Abstract: An acute and prolonged inflammation inhibits the reproduction process by the disruption of the neurohormonal activity of the hypothalamic-pituitary-gonadal axis. It is thought that these changes may be caused by proinflammatory cytokines, i.e., interleukin (IL) -1β, IL-6 and tumor necrosis factor (TNF) α. The aim of this study was to determine the effect of an acute and prolonged inflammation on the expression of genes encoding cytokine and their receptors, gonadotropin releasing hormone receptor (GnRHR), beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…On the other hand, TNF-α controls the intensity, e cacy, and duration of in ammatory reactions (Giovannini et al 2011). Therefore, the present data revealed the activation of acute phase reactants in response to in ammation caused by coal dust exposure in the study participants and also consolidate the earlier nding that acute and prolonged in ammation inhibits the reproduction process by activating proin ammatory cytokines, i.e., interleukin (IL) -1β, IL-6 and tumor necrosis factor (TNF) α and disrupting the neurohormonal activity of the hypothalamic-pituitary-gonadal axis (Wojtulewicz et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, TNF-α controls the intensity, e cacy, and duration of in ammatory reactions (Giovannini et al 2011). Therefore, the present data revealed the activation of acute phase reactants in response to in ammation caused by coal dust exposure in the study participants and also consolidate the earlier nding that acute and prolonged in ammation inhibits the reproduction process by activating proin ammatory cytokines, i.e., interleukin (IL) -1β, IL-6 and tumor necrosis factor (TNF) α and disrupting the neurohormonal activity of the hypothalamic-pituitary-gonadal axis (Wojtulewicz et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…When a prior LPS injection was made, there was no difference in the leptin peak concentration, but the leptin concentration decreased faster when a prior LPS injection was carried out in comparison to animals in the physiological state, which may suggest that either leptin had a faster metabolism or it bounded faster to its receptor to exert the effect. Moreover, leptin can bind not only to its receptor but also non-specifically to the IL-6 receptor (IL-6R) [ 29 ], and it is well documented that IL6-R expression is highly increased after LPS injection as well, which we also observed in acute stress conditions in sheep aorta [ 18 ], perivascular adipose tissue [ 19 ], hypothalamus [ 30 ] and anterior pituitary [ 21 ], but not in the prolonged inflammation in the anterior pituitary [ 31 ].…”
Section: Discussionmentioning
confidence: 91%
“…IL-2 deficiency can cause autoimmune inflammation with neuron damage [ 36 ]. The cytokines circulation (TNF-α, IL-1, IL-8) in the bloodstream usually indicates an acute phase of the body’s response to inflammation, which is regulated by proinflammatory (IFN-γ, IL-12) or anti-inflammatory (IL-10) cytokines [ 37 ]. We have found that the level of proinflammatory TNF-α, IL-7, and sCD40L increased in the blood plasma of DRE patients, and the anti-inflammatory IL-4 level has also increased compensatory.…”
Section: Discussionmentioning
confidence: 99%